1978
DOI: 10.1042/bj1710115
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a pH-dependent irreversible formation of a stable conformation of phenacyl-α-chymotrypsin

Abstract: A reinvestigation of the modification reactions of alpha-chymotrypsin with phenacyl bromide was carried out. Results conclusively demonstrate that the chemically and physically different modified enzymes prepared at pH 4 and at pH 7 both contain the phenacyl group at methionine-192 in the sulphonium salt form. Evidence to suppoort this conclusion derives from 13C nuclear-magnetic-resonance spectroscopic observations on [methylene-13C]phenacyl-enriched enzymes. More conclusively, the methionine-192-containing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is apparent that the predominant part of the radioactivity eluted in Fraction II indicating that the alkylated methionyl residue is located in the peptide with Lys-Pro-TyrHis-Thr-as the N-terminal sequence and the amino acid composition indicated that no cleavage had taken place at Met-398. To demonstrate conclusively the location of the alkylated methionyl residue it was utilized that peptides may be cleaved under mild conditions at alkylated methionyl residues by a mechanism similar to that responsible for the cleavage with cyanogen bromide ( 13,14). When fraction II was boiled in water cleavage took place at Met-398 producing a new N-terminal sequence, Val-Pro-Phe-AspVal-.…”
Section: Cyanogen Bromide Fragments Of Iaa-cpd-ymentioning
confidence: 99%
“…It is apparent that the predominant part of the radioactivity eluted in Fraction II indicating that the alkylated methionyl residue is located in the peptide with Lys-Pro-TyrHis-Thr-as the N-terminal sequence and the amino acid composition indicated that no cleavage had taken place at Met-398. To demonstrate conclusively the location of the alkylated methionyl residue it was utilized that peptides may be cleaved under mild conditions at alkylated methionyl residues by a mechanism similar to that responsible for the cleavage with cyanogen bromide ( 13,14). When fraction II was boiled in water cleavage took place at Met-398 producing a new N-terminal sequence, Val-Pro-Phe-AspVal-.…”
Section: Cyanogen Bromide Fragments Of Iaa-cpd-ymentioning
confidence: 99%
“…It has been noted that chymotrypsin modified with a-bromoacetophenone can be isolated at two conformational isomers, depending upon the solution pH used in preparation of the derivative (Mariano et al, 1978). In this work attempts to detect equilibration between 4-(trifluoromethyl)-a-bromoacetanilide-modified proteins prepared at pH 4.4 and 7 by fluorine spectroscopy produced no evidence for conformational isomerization.…”
Section: -(Trifluoromethyl)-a-bromoacetanilide Derivativementioning
confidence: 79%